Pengembangan Media Pembelajaran Berbasis Canva pada Mata Pelajaran Informatika Materi Analisis Data Kelas XA di MA Al Fattahiyyah - Aissyyah, Nik Matun Nur; Pamungkas, Bian Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to develop Canva based instructional media to enhance students’ interest and learning outcomes in the Data Analysis topic of the Informatics subject for class XA at MA Al Fattahiyyah. Initial observations showed that only 37% of students scored above the Minimum Competency Criteria (KKM) and demonstrated passive and unenthusiastic behavior during lessons. The research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The developed product is an interactive video slide that includes learning objectives, motivation, core material delivery, and practice quizzes. Validation results revealed that the media is highly valid with scores of 95% from content experts and 88.75% from media experts. Student trials yielded 91.86% (small group) and 89.47% (large group), categorized as highly appropriate. These findings indicate that Canva-based instructional media is effective and feasible for enhancing Informatics learning, particularly in the Data Analysis topic.